(3QSGdI aj CeQ GSJVGAI GdLhs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3SCdfi habc Gdg hEjGfG HGdUhGH Cf CYjO HGdGNJUGQ eeG CbQH HOhf hNGdaI GdLeghQ ai GeQ ESJVGAI GdLh aCLHJc eG QhGO GdJObjb hGdJMbjb ajg abO HGfJ ai Pdc eHGdZI HMSH hVZi s
(3BNQgG (B:s
(3jMOK Yf GSJVGA aGdCeQ dGjMJGL ZdG Cf CTQMg abO HGdZfGajg ai ehGVY CNQi hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B(423(7)) s
Keywords: (3GdadSaI hGdefWbs